The Ovine Stifle as a Model for Human Cruciate Ligament Surgery - Radford, W.J.P.; Amis, A. A.; Stead, A. C. (Veterinary and Comparative Orthopaedics and Traumatology, 1996)
This study evaluated the anatomy and biomechanics of the ovine stifle, with a view to its use as a model of the human knee joint.Stifles were dissected to define the internal anatomy, concentrating on the cruciate ligaments. The cranial cruciate ligament (CraCL) was assessed biomechanically at 30° and 90° flexion, intact, with the craniomedial bundle (CraMB) divided, and after complete transection. Craniocaudal (C-C) and internal-external rotatory stability were assessed. The tensile strength of the CraCL was determined.The morphology of the ovine stifle was similar to the human knee. Sequential sectioning of the bundles of the CraCL caused increasing cranial laxity of the joint. Rotational laxity also increased as the CraCL was divided, as well as with progressive joint flexion. It was concluded that the ovine stifle is a valid animal model for the human knee for work on the cruciate ligaments.The anatomy and biomechanics of the ovine stifle were studied, with a view to assessing the suitability of the joint as a surgical model for the cruciate ligaments of the human knee. The ligaments, joint stability and cranial cruciate ligament strength were measured. It was concluded that the ovine stifle is a valid model of the human knee for this purpose.
Keywords: Cruciate ligament; ovine; stifle joint; anatomy; biomechanics